High energy density at high temperature in PLZST antiferroelectric ceramics. Issue 15 (27th March 2019) - Liu, Pin; Fan, Baoyan; Yang, Guang; Li, Wenru; Zhang, Haibo; Jiang, Shenglin
Abstract : PLZST ceramics possess good energy density at high temperature (100–175 °C) due to phase transitions. Abstract : A high operating temperature of antiferroelectric (AFE) materials for energy storage applications is preferred to meet the rising demand under extreme conditions. However, most of the reported PLZST ceramics possess low energy density as the temperature rises to 120 °C. In this work, (Pb0.97 La0.02 )(Zr0.93 Sn0.03 Ti0.04 )O3 orthorhombic ceramics are designed to acquire high energy density under high temperature, via fine-tuning the ratio of Zr/Sn/Ti. Due to the orthorhombic to tetragonal phase transition behavior and the high T C point, the ceramics possess good energy density (2.0–3.4 J cm −3 ) at high temperature (100–175 °C) rather than room temperature. The trend of the temperature-dependent energy density is antithetic with that of most reported results. It demonstrates that PLZST orthorhombic AFE ceramics are promising energy storage materials at high temperature. Meanwhile, this work provides the idea of acquiring high temperature stability by compositing different phases with opposite trends of temperature-dependent energy density.